Lawrence Tremper account books and journal - Tremper, Lawrence
Account books (1781-1783) and journal (1783 March 21-1784 December 21) kept by Tremper as an army quartermaster in New York.
Continental and U.S. army officer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: United States. -- Army -- Supplies and stores; United States. -- Continental Army -- Supplies and stores; Quartermasters -- New York (State); New York (State) -- History -- Revolution, 1775-1783.; United States -- History -- Revolution, 1775-1783.; Army officers